Concurrent chemoradiotherapy compared with surgery and adjuvant radiotherapy for oral cavity squamous cell carcinoma. Issue 4 (2nd May 2014) - Gore, Sinclair M.; Crombie, Anthony K.; Batstone, Martin D.; Clark, Jonathan R.
Abstract: Background: The purpose of this study was to compare survival and functional outcomes in patients with advanced oral cavity squamous cell carcinoma (SCC) treated with either surgery + adjuvant radiotherapy (RT) or concurrent chemoradiotherapy (CRT). Methods: Patients treated with curative intent by either surgery + RT or concurrent CRT were identified over a 6‐year period (2001–2007). Disease and functional outcomes were analyzed on an intention‐to‐treat basis. Results: Fifty‐four patients underwent surgical excision and received postoperative RT. Fifty patients underwent concurrent CRT. Overall survival (OS) and disease‐specific survival (DSS) was significantly higher in the surgically treated group ( p < .001). Long‐term enteral feeding tube support was more commonly required in those treated with CRT, whereas osteoradionecrosis rates were comparable between the 2 groups. Conclusion: Treatment by surgery + adjuvant RT for advanced oral cavity SCC resulted in better disease control than treatment with CRT. This supports traditional surgical treatment algorithms for oral cavity cancer. © 2014 Wiley Periodicals, Inc. Head Neck 37 : 518–523, 2015